Mesoporous silica/reduced graphene oxide composite for fluoxetine and trimethoprim adsorption - Dogan, Ali Dogancan; Yilmaz, Muge Sari; Erkan, Hanife Sari (ELSEVIER, 2025)
In this study, a mesoporous silica/reduced graphene oxide (MS-rGO) composite was synthesised and characterised for the adsorption of two persistent pharmaceutical micropollutants, fluoxetine (FLX) and trimethoprim (TMP), from water. The adsorption performance of the MS-rGO composite was evaluated under various conditions including adsorbent dosage, pH, initial drug concentration, time and temperature. The results showed effective removal of both drugs, with FLX adsorption capacity reaching 13.07 mg/g (corresponding to 74.8 % removal) under conditions of 0.0025 g MS-rGO, pH 8 and 15 min, and TMP adsorption capacity reaching 17.60 mg/g (88.1 % removal) under conditions of 0.0025 g MS-rGO, pH 9 and 30 min, both at an initial concentration of 5 mg/L. Adsorption followed pseudo-second-order kinetics (R-2 > 0.9977) and Langmuir isotherm models (R-2 > 0.9921) with maximum capacities of 102.04 mg/g for FLX and 52.91 mg/g for TMP. Thermodynamic parameters (Delta H degrees, Delta S degrees, Delta G degrees) confirmed that the adsorption was endothermic and spontaneous, mainly driven by electrostatic interactions between the MS-rGO composite and the drugs. These results highlight the potential of the MS-rGO composite as a promising adsorbent for the removal of pharmaceutical micropollutants from aqueous systems, offering rapid adsorption in a short time; however, its reusability is limited, with removal efficiencies decreasing by almost 50 % after three cycles.
Keywords: Micropollutants; Adsorption; Composite material; Fluoxetine; Trimethoprim; PERSONAL CARE PRODUCTS; ACTIVATED-SLUDGE; REMOVAL; WATER; PHARMACEUTICALS; SULFAMETHOXAZOLE; SILICA; ANTIBIOTICS; PERFORMANCE; SEWAGE; Chemistry; Science & Technology - Other Topics; Materials Science